Development of Antibody-Tagged Nanoparticles for Detection of Transplant Rejection Using Biomagnetic Sensors. Issue 10 (October 2013) - Butler, Kimberly S.; Lovato, Debbie M.; Adolphi, Natalie L.; Belfon, Robert; Fegan, Danielle L.; Monson, Todd C.; Hathaway, Helen J.; Huber, Dale L.; Tessier, T. E.; Bryant, H. C.; Flynn, Edward R.; Larson, Richard S.
Organ transplantation is a life-saving procedure and the preferred method of treatment for a growing number of disease states. The advent of new immunosuppressants and improved care has led to great advances in both patient and graft survival. However, acute T-cell-mediated graft rejection occurs in a significant quantity of recipients and remains a life-threatening condition. Acute rejection is associated with decrease in long-term graft survival, demonstrating a need to carefully monitor transplant patients. Current diagnostic criteria for transplant rejection rely on invasive tissue biopsies or relatively nonspecific clinical features. A noninvasive way is needed to detect, localize, and monitor transplant rejection. Capitalizing on advances in targeted contrast agents and magnetic-based detection technology, we developed anti-CD3 antibody-tagged nanoparticles. T cells were found to bind preferentially to antibody-tagged nanoparticles, as identified through light microscopy, transmission electron microscopy, and confocal microscopy. Using mouse skin graft models, we were also able to demonstrate in vivo vascular delivery of T-cell targeted nanoparticles. We conclude that targeting lymphocytes with magnetic nanoparticles is conducive to developing a novel, noninvasive strategy for identifying transplant rejection.